HUBUNGAN HIGIENE SANITASI DENGAN KANDUNGAN ESCHERICHIA COLI PADA ES BATU INDUSTRI RUMAH TANGGA DI TEPI JALAN WAHID HASYIM 2 KECAMATAN SEMPAJA KOTA SAMARINDA TAHUN 2015 - Suwignyo Suwignyo; Abdul Rachim; Arizal Sapitri (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2016)
Ice is a water that cooled below 0 °C and used for complement in drink. Ice can be found almost everywhere, including in the Wahid Hasyim Sempaja Roadside. From the preliminary test, obtained 5 samples ice cube were contaminated by Escherichia coli. The purpose of this study was to determine relationship between hygiene and sanitation with presence of Eschericia coli in ice cube of home industry at Wahid Hasyim Roadside Samarinda. This research used quantitative with survey methode. The population in this study was all of the seller in 2nd Wahid Hasyim Roadside. Sample was taken by Krejcie and Morgan so the there were 44 samples and used Cluster Random Sampling. The instruments are questionnaries, observation and laboratory test. Data analysis was carried out univariate and bivariate (using Fisher test p= 0.05). The conclusion of this study there are a relation between chosing raw material (p=0,03) and saving raw material (p=0,03) with presence of Eschericia coli. There was no relation between processing raw material into ice cube with presence of Eschericia coli (p=0,15).Advice that can be given to ice cube should maintain hygiene and sanitation of the selection, processing and storage of ice cube.